Curse and blessing: The effect of the dividend ban on euro area bank valuations and syndicated lending - Sanders, Emiel; Simoens, Mathieu; Vander Vennet, Rudi (Journal of Banking & Finance, 2024)
At the outbreak of the Covid-19 pandemic, the European Central Bank issued a strong recommendation towards banks to halt dividend payouts. The goal of this de facto dividend ban was to boost banks' capital to ensure the supply of credit. However, given the importance of dividends for investors, this unprecedented measure is likely to have impacted bank valuations. Hence, banks may have chosen to preserve their higher capital buffers to boost payouts after the lifting of the ban, rendering the intended positive effect on credit supply a priori uncertain. We first investigate the effect of the dividend ban announcement on euro area banks' valuations and find a significantly negative impact. Second, we show that banks significantly expanded credit supply in the syndicated loan market, without counteracting effect of the negative stock market reaction. Our findings are corroborated when we exploit the multi-bank nature of syndicated loans in a within-loan setup.